Equine papillomavirus type 2: An equine equivalent to human papillomavirus 16?. (July 2017) - Sykora, S.; Jindra, C.; Hofer, M.; Steinborn, R.; Brandt, S.
Highlights: The physical form of equine papillomavirus type 2 (EcPV2) in equine squamous cell carcinomas (SCC) and smegma was studied. More than half of the cases were shown to harbour virion-like structures. E6/E2 qPCR results indicated EcPV2 integration into the host cell genome. Smegma represents a rich EcPV2 reservoir. EcPV2 infection may be aetiologically associated with a subset of SCCs of the head. Abstract: In horses, squamous cell carcinomas (SCC) commonly affect the external genitals. There is growing evidence that equine papillomavirus type 2 (EcPV2) infection promotes disease development. To assess the possible association of EcPV2 with equine SCCs of the head (HSCC), 15 HSCC DNA samples were screened by E6/E7, E2, and LCR PCR and amplicons were analysed for sequence variations. The physical form of EcPV2 in HSCC, genital lesions, and smegma from horses with SCC was then addressed using EcPV2 immunocapture PCR (IC/PCR) for detection of virion, and E6 vs. E2 qPCR to investigate possible integration events. Four of 15 HSCC tested positive for EcPV2 DNA and harboured known or novel genetic variants of E6, E7, E2 and the LCR. Eighteen of 35 sample extracts including 3/4 smegma samples scored positive by IC/PCR, suggesting that about 51% of tested extracts harboured virions. E6/E2 qPCR from tumour DNA revealed E2/E6 copies/cell ranging between <1 (E2; E6) and 797 (E2) or 1434 (E6). IC/PCR-positive smegma samples contained higher E2 and E6 copy numbers, ranging between 1490 and 4.95 × 10 5 (E2) or 2227 and 8.54 × 10 5 (E6) copies/cell. Together with IC/PCR results, this finding suggests that smegma can serve as a rich EcPV2 reservoir. HSCCs harboured significantly lower viral DNA amounts (<1–25 copies/cell) than most genital tumour and smegma DNA isolates. The majority of samples contained more E6 than E2 DNA, with E6:E2 ratios ranging between 0.88 and 4.12. Although not statistically significant ( P > 0.05), this finding suggests that EcPV2 can integrate into the equine host cell genome.